PERAN KARAKTERISTIK KEPRIBADIAN, LEADER MEMBER EXCHANGE, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT.MATAHARI SILVERINDO JAYA (MSJ) SEMARANG - Muhaimin .; Kunartinah .; Kis Indriyaningrum (Jurnal Bisnis dan Ekonomi, 2011)
This study aimed to determine the effect of personality characteristics, leader member exchange and work environment on performance. To analyze the effect, the data were analyzed using a quantitative analysis of themultiple linear regression. The results showed that the characteristics of personality (Big Five Personality) did not affect positively and significantly. While the leader member exchange and work environment is positive andsignificant. The results of the model test study "Effect of personality characteristics, leader member exchange and work environment on performance", only able to explain changes in performance of 43.5% while the remaining 56.5% change in employee performance is explained by other variables / factors that influence the performance of employees were not studied. Based on these results, it is recommended that (1) Placement of employees adjusted to the characteristics of personality with reference to the abilities and talents of employee interests. (2) An employer must be able to establish a better relationship with their subordinates, so hopefully there will be mutual influence of the subordinates by showing good performance. (3) Conditions of work environments in particular physical environment improved and equipped so as to support the execution of tasks and jobs of the employees.Key words: big five personality, leader member exchange, work environment, and performance.